World Englishes : Overview - Anchimbe, Eric (The Encyclopedia of Applied Linguistics. 2nd Edition, 2026)
Since the 1970s, “World Englishes” (WEs) has developed into an encompassing research field. Its main focus has been on categorizing, describing, and studying the English language as used in different parts of the world. Initially viewing the varieties as deviations from the so-called native standard English, the field has evolved significantly over the years and now considers all varieties of the language as outcomes of similar evolutionary processes, hence the egalitarian appellation “World Englishes.” Braj Kachru's Three Circles Model triggered a shift in research attention from the political and colonial perceptions of non-native Englishes to linguistic investigations of their emergence, evolution, and sociolinguistic features. This shift placed these new varieties, theoretically, on a similar level as the native varieties. Since then, feature analysis, processes of nativization, language attitudes, identity construction, and the functions and educational implications of English in the new locations have been the dominant lines of research. This overview discusses the asymmetrical dichotomies in earlier categorizations of English and the suitability of five recent theories in WEs research: Dynamic Model of Postcolonial English, Cognitive Contact Linguistics, Variational Pragmatics, Postcolonial Pragmatics, and Cultural Linguistics.
Keywords: World Englishes; Three Circles Model; Dynamic Model of Postcolonial English; Postcolonial Pragmatics; evolutionary processes